Response surface analysis of ultrasound and dynamic maceration extractions of Arbutus Unedo - Derbassi, Nabila Ben (2021)
The use of natural plant extracts in the food industry has been common practice for many decades, but, due to the pursuit of healthier diets by consumers, has gained a new momentum, in which natural food additives, namely preservatives have been extracted from plants. The most prominent example is the use of rosemary extract (E392) as a food preservative throughout the European Union, paving the way for new extracts to be used for the same purpose, possibly with better results. In this work, the extraction of leafy parts of Arbutus unedo L. is described both through ultrasound assisted extraction (UAE) and dynamic maceration (DM), following an optimization through Response Surface Methodology (RSM) to optimize the extraction yield. For the DM the factors analyzed were (F1) “Time” which varied between 10 and 60 minutes, (F2) “Temperature” which varied between 30 and 80 ºC, and finally (F3) “Solvent” (ethanol) which varied between 0 and 100%. For the UAE, the factors were also (F3) “Solvent” and (F1) “Time”, and although the variation in solvent was the same, the time of extraction only varied between 5 and 30 minutes. Finally, the third factor was ultrasonic (F2) “Power” of the equipment that varied between 50 and 500 watts. The analyzed response for both extractions were the dry residue (Y1) which varied between 3 and 65.3 mg for UAE and 10.4 and 99.9 mg for DM. The RSM analysis rendered a quadratic model with an inverse transformation for DM, and a reduced quadratic model with no transformation for UAE. To optimize the yield of dry residue (Y1), optimization studies were performed and indicated the optimal points at which a higher yield of dry residue can be obtained, and were F1 – 57 minutes, F2 – 46 ºC and F3 – 52% of ethanol for the DM extraction. For UAE, the optimal points for the same Y1 response were F1 – 17 minutes, F2 – 380 watts and F3 – 39% of ethanol. In Figure 1 , it is clear that for DM a longer time of extraction favors the residue yield, as well as a temperature near 60 ºC, while for the UAE, time did not seem such an important factor, while the power of the ultrasonic probe was quite important. Overall, due to the lower amount of ethanol needed and the lower extraction time, UAE seems to be the best extraction technique to maximize the yield of dry residue of A. unedo , although in terms of mass, DM yielded 99 mg while UAE only 65.3mg. Other responses are currently being studied to determine the best overall extraction technique.